Faktor Resiko Kejadian Anemia Pada Balita Usia 6-59 Bulan di Kelurahan Way Lunik Kecamatan Panjang Kota Bandar Lampung - Monica Bela Dwi Sintia; Aryanti Wardiyah; Linawati Novikasari (Malahayati Nursing Journal, 2025)
ABSTRACT Anemia is a condition in which the hemoglobin is below the normal value (11g/dL). According to World Health Organization in 2023, the prevalence of anemia among toddlers aged 6-59 month in 2019 reached 39,8%, equivalent to 269 million toddlers suffering anemia. To determine the association of risk factors of anemia among toddlers aged 6-59 months in the district of Way Lunik sub-district of Panjang of Bandar Lampung city in 2024. Quantitative research with a cross sectional approach. The population consists of 625 toddlers aged 6-59 months in Way Lunik sub-district Panjang sub-district Bandar Lampung City, with a sample of 244 respondents. The sampling technique is purposive sampling technique. Data analysis used the chi-square test. In the study, it was shown that 69.7% of toddlers under five experienced anemia. Those aged ≥25 months accounted for 75.8%. Non-exclusive breastfeeding history was 62.7%. Birth weight ≥2,500 grams was 92.2%. Male gender was 60.7%.  Mother who did not work were 56.6%. Mother with education less than high school were 56,6%. There is no association between toddlers' age and the occurrence of anemia (p-value 0.11, OR 1.741). There is an association between exclusive breastfeeding and the occurrence of anemia (p-value 0.001, OR 8.767). There is no association between birth weight and the occurrence of anemia (p-value 0.360, OR 1.694). There is no association between gender and the occurrence of anemia (p-value 0.164, OR 0.675). There is no association between mothers' occupations and the occurrence of anemia (p-value 0.564, OR 0.845). There is an association between mothers' education and the occurrence of anemia (p-value 0.001, OR 4.241) among toddlers aged 6-59 months in Way Lunik district, Panjang Subdistrict, Bandar Lampung City, in 2024. Keywords: Anemia, Toddler Age, History of Exclusive Breastfeeding, Birth Weight, Gender, Mother Occupation, Mother Education  ABSTRAK Anemia adalah suatu kondisi di mana kadar hemoglobin barada di bawah nilai normal (11g/dL) menurut WHO tahun 2023, prevalensi anemia pada balita usia 6-59 bulan di tahun 2019 mencapai 39,8% atau setara dengan 269 juta balita. Diketahui faktor resiko kejadian anemia pada balita usia 6-59 bulan di Kelurahan Way Lunik Kecamatan Panjang Kota Bandar Lampung Tahun 2024. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi 625 balita usia 6-59 bulan di Kelurahan Way Lunik Kecamatan Panjang Kota Bandar Lampung dengan sampel 244 responden. Teknik sampel purposive sampling. Analisis data menggunakan uji chi-square. Dalam penelitian ini menunjukkan bahwa balita yang mengalami kejadian anemia sebanyak 69,7%. Usia ³25 bulan Sebanyak 75,8%. Riwayat asi tidak eksklusif sebanyak 62,7%. Berat badan lahir ³2.500-gram sebanyak 92,2%. Jenis kelamin laki-laki sebanyak 60,7%. Ibu yang tidak bekerja sebanyak 56,6%. Ibu yang memiliki pendidikan SMA sebanyak 56,6%. Tidak ada hubungan antara usia balita dengan kejadian anemia (p-value 0,11. OR 1,741). Terdapat hubungan antara asi eksklusif dengan kejadian anemia (p-value 0,001. OR 8,767). Tidak ada hubungan antara berat badan lahir dengan kejadian anemia (p-value 0,360. OR 1,694). Tidak ada hubungan antara jenis kelamin dengan kejadian anemia (p-value 0,164. OR 0,675). Tidak ada hubungan antara pekerjaan ibu dengan kejadian anemia (p-value 564. OR 0,845). Ada hubungan antara pendidikan ibu dengan kejadian anemia (p-value 0,001. OR 4,241) pada balita usia 6-59 bulan di Kelurahan Way Lunik Kecamatan Panjang Kota Bandar Lampung Tahun 2024. Kata Kunci: Anemia, Usia Balita, Riwayat Asi, Berat Badan Lahir, Jenis Kelamin, Pekerjaan Ibu, Pendidikan Ibu.